Realisability conditions for second‐order marginals of biphased media. Issue 3 (7th May 2014) - Lachièze‐Rey, Raphaël
Abstract This paper concerns the second‐order marginals of biphased random media. We give discriminating necessary conditions for a bivariate function to be such a valid marginal, along with an algorithmic implementation, and illustrate our study with two theoretical applications: (1) the spherical variograms are valid indicator variograms if and only if they are multiplied by a sufficiently small constant, which upper bound is estimated, and (2) not every covariance/indicator variogram can be obtained with a Gaussian level set. © 2014 Wiley Periodicals, Inc. Random Struct. Alg., 47, 588–604, 2015